Bacteria in Ostreococcus tauri cultures – friends, foes or hitchhikers? - Abby, Sophie S.; Touchon, Marie; De Jode, Aurelien; Grimsley, Nigel; Piganeau, Gwenael (Frontiers in Microbiology, 2014)
Marine phytoplankton produce half of the oxygen we breathe and their astounding diversity is just starting to be unravelled. Many microbial phytoplankton are thought to be phototrophic, depending solely on inorganic sources of carbon and minerals for growth rather than preying on other planktonic cells. However, there is increasing evidence that symbiotic associations, to a large extent with bacteria, are required for vitamin or nutrient uptake for many eukaryotic microalgae. Here, we use in silico approaches to look for putative symbiotic interactions by analysing the gene content of microbial communities associated with 13 different Ostreococcus tauri (Chlorophyta, Mamilleophyceae) cultures sampled from the Mediterranean Sea. While we find evidence for bacteria in all cultures, there is no ubiquitous bacterial group, and the most prevalent group, Flavobacteria, is present in 10 out of 13 cultures. We detected genes predicted to encode at least 7 type 3 secretion systems (T3SS) and 6 putative T6SS in 7 microbiomes. Phylogenetic analyses show that the corresponding genes are closely related to genes of systems identified in bacterial-plant interactions, suggesting that these T3SS might be involved in cell-to-cell interactions with O. tauri.